PENGARUH SEDUHAN DAUN MINT DENGAN MADU TERHADAP PENURUNAN EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I - Nelli, Ermeida (Politeknik Tiara Bunda, 2025)
Background: Nausea and vomiting that occurs in the first trimester of pregnancy are caused by increased levels of the hormone Estrogen and Human Chorionic Gonadotropine (HCG). Emesis gravidarum causes disruption of activity, decreases appetite and occurs dehydration. According to World Health data Organization (WHO)2021, the number of cases of hyperemesis gravidarum reached 12.5% in the world. Meanwhile in Indonesiait reached 14.8%. The purpose of this study To know the effect of steeping mint leaves with honey on reducing emesis gravidarum in first trimester pregnant women at Rani Kusuma Kabupaten Tangerang. Research Methods: The research method of this type of research is pre-experimental using a one group pretest-postest design in one group, using a total sampling technique with a sample size of 10 respondents. Results: The results of the Wilcoxon test obtained a p-value of 0.008 <0.05, so Ha is accepted, meaning that there is a difference between the level of emesis gravidarum (nausea and vomiting) before and after being given mint leaves with honey, meaning that there is an effect of steeping mint leaves with honey on reducing emesis gravidarum in first trimester pregnant women at the Rani Kusuma, Kabupaten Tangerang. Conclusion: Steeping mint leaves with honey has an effect on reducing Emesis Gravidarum in first trimester pregnant women,